Comparison of Variations in the Angle of the 0° and 10° Cephalad Beam Direction in Anteroposterior (AP) Projection Pedical Examination to Show More Informative Anatomy - Mareta, Santa; Dewilza, Nerifa; Nansih, Livia Ade; Balkis, Sintia (PT. Hafasy Dwi Nawasena, 2026)
The anteroposterior (AP) projection of the Ossa Pedis examination technique in some hospitals typically uses a perpendicular 0° beam angle, while the theoretical approach uses a 10° cephalad beam angle. This study aims to compare variations in 0° and 10° cephalad beam angles and provide more informative anatomical information. The study used a quantitative experimental approach in the Radiology Laboratory of the Faculty of Vocational Studies, Baiturrahmah University, from June to August 2025. The study involved a population of 79 individuals and a sample size of 3 individuals. Data were collected through radiographic images and then assessed by 5 radiology specialists and 25 radiographers using a questionnaire with a 5-item Likert scale. Question 1 depicts the anatomy of the tarsal bones, Question 2 depicts the space between the metatarsals, Question 3 depicts the lower part of the metatarsals, Question 4 depicts the joint space between the medial cuneiform and the intermedial cuneiform, Question 5 depicts the joint space between the interphalangeal joint, metatarsophalangeal joint, and tarsometatarsal joint. Data processing using SPSS with the Wilcoxon test is presented in figures and tables. Based on the results, the 0° angle produced a lower average value of 17.64, while the 10° cephalad angle produced a more optimal image with a higher average value of 22.72. This image has the advantage of a more open joint space, a more defined metatarsal base, and clearer alignment of the foot bones due to reduced superposition. With a p-value of <0.005, it can be concluded that there are differences in the anatomical images in the anteroposterior (AP) projection pedis examination at 0° and 10° cephalad angles.